2017
DOI: 10.4236/jmmce.2017.52008
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption and Post Adsorption Behavior of Schwertmannite with Various Oxyanions

Abstract: The adsorption and post adsorption behavior of schwertmannite with various oxyanions were investigated for clean-up contaminated water with hazardous oxyanions and safe disposal of spent schwertmannite. The result of adsorption experiments showed that the maximum capacities of oxyanions adsorption onto schwertmannite are 1.023, 0.934, 0.723 and 0.313 mmol/g for arsenate, phosphate, chromate and selenate, respectively. Based on the differences in the adsorption capacities, the selectivity of oxyanion adsorption… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 24 publications
0
14
0
Order By: Relevance
“…As reported by several authors, Cr(VI) adsorption on schwertmannite can be mainly attributed to ion exchange with SO 4 2 − groups [ 22 , 25 , 52 , 71 ]. Due to the same charge and a similar radius of SO 4 2 − (0.23 nm) and CrO 4 2 − (0.24 nm) ions, the replacement of sulphate groups with chromate groups occurs without changing the crystal structure of the schwertmannite [ 52 ].…”
Section: Resultsmentioning
confidence: 77%
See 2 more Smart Citations
“…As reported by several authors, Cr(VI) adsorption on schwertmannite can be mainly attributed to ion exchange with SO 4 2 − groups [ 22 , 25 , 52 , 71 ]. Due to the same charge and a similar radius of SO 4 2 − (0.23 nm) and CrO 4 2 − (0.24 nm) ions, the replacement of sulphate groups with chromate groups occurs without changing the crystal structure of the schwertmannite [ 52 ].…”
Section: Resultsmentioning
confidence: 77%
“…Khamphila and co-workers found that the adsorption of Cr(VI) on easily accessible active sites during the fast initial stage is likely to be ion exchange with SO 4 2 – groups. In contrast, the second stage involves the slow diffusion of Cr(VI) from the surface sites into the interior of the adsorbent and the formation of complexes [ 25 ]. According to Zhang and co-workers, two types of surface complexes can form on the schwertmannite surface: monodentate (≡FeOCrO 3 − ) and bidentate (≡Fe 2 O 2 CrO 2 ) [ 52 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…oxyanions are absorbed by the 2 nd mechanism. The adsorption and post adsorption behaviour of Sch towards various oxyanions were investigated by Khamphila et al 103 The results implied that the . One is to directly stabilize it and the other is to oxidate it rst and then chemically stabilizes it.…”
Section: àmentioning
confidence: 99%
“…1.8). These secondary Fe minerals sequester metals, removing them from solution (Ahoranta, 2016;Khamphila et al, 2017;Shu et al, 2019). Burgos et al (2012) compared the sequestration of metals by schwertmannite formed at low pH (2.5 -4.0) by biological Fe(II) oxidation to the chemical formation of ferrihydrite [Fe 10 O 14 (OH) 2 ] at higher pH (4.4 -8.4).…”
Section: Accepted Articlementioning
confidence: 99%